CD200 in acute myeloid leukemia: marked upregulation in CEBPA biallelic mutated cases - Laura González-Guerrero; Helena Castellet; Clara Martínez; Nuria González; Francesca Guijarro; Natalia Lloveras; Marta Pratcorona; Ignasi Gich; Pau Berenguer-Molins; Júlia Perera-Bel; Lurdes Zamora; Martí Mascaró; et al. (Diagnostic Pathology)
Abstract CD200 is a glycoprotein that binds with its receptor CD200R, providing immunosuppressive signals to T and NK cells. CD200 is expressed by normal stem cells and progenitors committed to B-lymphopoiesis and myeloid development. CD200 biological relevance in acute leukemias is only partially understood. The study included a consecutive series of four hundred thirty-one patients with acute myeloid leukemia (AML). Immunophenotype was established by multiparametric flow cytometry, and the genetic diagnosis was performed by PCR-based methods and a targeted resequencing method covering 42 genes. 66% of AML patients expressed CD200 being significantly associated with CD34 reactivity. The frequency of CD200 positivity was higher in cases with core-binding factor genetic lesions such as RUNX1-RUNX1T1 (81.3%) fusions and CBFB-MHY11 (63.2%) rearrangements and also with biallelic CEBPA mutations (100%). The molecular AML group with the lowest CD200 reactivity (19.1%) corresponded to AML with NPM1 mutations. RNA seq showed no uniform pattern of infiltrating cells in CEBPA mutated AML. Deconvolution analysis may be used to assess the immunoregulatory mechanisms of AML. CD200 expression could help identify the more immature compartment and, combined with other markers, single out CEPA-mutated AML.